2016
DOI: 10.18632/oncotarget.10646
|View full text |Cite
|
Sign up to set email alerts
|

Pregnane X-receptor promotes stem cell-mediated colon cancer relapse

Abstract: Colorectal cancer lethality usually results from post-treatment relapse in the majority of stage II-IV patients, due to the enhanced resistance of Cancer Stem Cells (CSCs). Here, we show that the nuclear receptor Pregnane X Receptor (PXR, NR1I2), behaves as a key driver of CSC-mediated tumor recurrence. First, PXR is specifically expressed in CSCs, where it drives the expression of genes involved in self-renewal and chemoresistance. Clinically, high levels of PXR correlate with poor recurrence-free survival in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 56 publications
0
51
0
1
Order By: Relevance
“…BEL Attenuates RIF-Induced Resistance to SN-38. Previous studies have shown that elevated levels of PXR-mediated expression of drug-metabolizing enzymes and drug-efflux pumps in cancer cells contribute to increased resistance toward chemotherapy drugs (Pondugula and Mani, 2013;Planque et al, 2016;Pondugula et al, 2016). For instance, the activation of hPXR-mediated expression of drug-metabolizing enzymes and drug-efflux pumps decreases the sensitivity of human colon cancer cells, including LS174T cells, to several chemotherapy drugs such as SN-38 [the active metabolite of irinotecan (C 22 H 20 N 2 O 5 )] (Pondugula et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…BEL Attenuates RIF-Induced Resistance to SN-38. Previous studies have shown that elevated levels of PXR-mediated expression of drug-metabolizing enzymes and drug-efflux pumps in cancer cells contribute to increased resistance toward chemotherapy drugs (Pondugula and Mani, 2013;Planque et al, 2016;Pondugula et al, 2016). For instance, the activation of hPXR-mediated expression of drug-metabolizing enzymes and drug-efflux pumps decreases the sensitivity of human colon cancer cells, including LS174T cells, to several chemotherapy drugs such as SN-38 [the active metabolite of irinotecan (C 22 H 20 N 2 O 5 )] (Pondugula et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…50,000 cells were subcutaneously injected into nude mice in Matrigel – DMEM (v : v). 50mg/kg 5-FU + 30mg/kg Irinotecan treatment (two i.p injection a week), was initiated once tumor reached 100 mm 3 [62]. These studies were approved by the ethics committee of the Languedoc Roussillon Region and carried out in compliance with the CNRS and INSERM ethical guidelines of animal experimentation (CEEA-LR-12051).…”
Section: Methodsmentioning
confidence: 99%
“…by regulating a network of downstream genes involved in self-renewal and chemoresistance [75]. PXR expression is associated with CSC enrichment, after cell sorting of cancer cells using ALDH activity to identify CSCs and after spheroid passaging.…”
Section: Planque Et Al Have Recently Demonstrated That Pxr Is a Potementioning
confidence: 99%
“…PXR expression is associated with CSC enrichment, after cell sorting of cancer cells using ALDH activity to identify CSCs and after spheroid passaging. In addition, expression of CSC markers and self-renewal are increased in CRC cells with enhanced PXR transcriptional activity [75]. PXR expression in intestinal CSCs is also associated with tumor aggressiveness and chemoresistance [76].…”
Section: Planque Et Al Have Recently Demonstrated That Pxr Is a Potementioning
confidence: 99%
See 1 more Smart Citation